Helminth communities of two populations of Myotis chiloensis (Chiroptera: Vespertilionidae) from Argentinean Patagonia - Falconaro, Antonella Carla (2018)
Most of the studies on chiropteran endoparasites in Argentina come from the Central and Northeast regions of the country, and there is only one parasitological study of bats from the Argentinean Patagonia. The aim of this study is to describe the helminth fauna of 42 Myotis chiloensis, comparing the composition and the structure of the endoparasite communities between two populations, inhabiting different environments in Andean humid forest and the ecotone between forest and Patagonian steppe. A total of 697 helminths were recovered from 33 bats: five species of trematodes, Ochoterenatrema sp., Paralecithodendrium sp., Parabascus limatulus, Parabascus sp., and Postorchigenes cf. joannae, two species of cestodes, Vampirolepis sp. 1 and Vampirolepis sp. 2, and three species of nematodes, Allintoshius baudi, Physaloptera sp., and Physocephalus sp. All the helminths, but Physocephalus sp., were recovered from the small and large intestine. This is the first survey of M. chiloensis’ helminth fauna. All the species, but A. baudi, represent new records of helminths in Patagonian bats. There were differences of parasite species richness between localities and both bat populations share almost half of the endoparasite species. Different preferences for intestinal regions were found for three species of trematodes in the bats from the site in the humid forest. Myotis chiloensis serves as both a definitive and intermediate host for endoparasites in the Patagonian ecosystem.